2022
DOI: 10.1186/s13063-022-06616-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of continuing versus withholding angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers on mortality and major adverse cardiovascular events in hypertensive patients undergoing elective non-cardiac surgery: study protocol for a multi-centric open-label randomised controlled trial

Abstract: Background Angiotensin-converting enzyme inhibitors (ACEIs)/angiotensin receptor blockers (ARBs) are commonly prescribed to patients with hypertension. These drugs are cardioprotective in addition to their blood pressure-lowering effects. However, it is debatable whether hypertensive patients who present for non-cardiac surgery should continue or discontinue these drugs preoperatively. Continuing the drugs entails the risk of perioperative refractory hypotension and/or angioneurotic oedema, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Three large, randomized trials addressing the effect of various perioperative management strategies of angiotensin-converting enzyme inhibitor/angiotensin receptor blocker medication on important renal and other outcomes are ongoing or recently completed. 44–46 The modest association between nadir hemoglobin concentration on postoperative day 1 and AKI in model 2 is consistent with previous data showing an association between postoperative bleeding and AKI in patients undergoing noncardiac surgery. 10 However, the POISE-3 trial of tranexamic acid versus placebo in patients undergoing noncardiac surgery found no effect of this strategy on AKI despite reducing both major bleeding and the proportion of patients administered a perioperative packed red cell transfusion, highlighting the complexity of the anemia–AKI association.…”
Section: Discussionsupporting
confidence: 89%
“…Three large, randomized trials addressing the effect of various perioperative management strategies of angiotensin-converting enzyme inhibitor/angiotensin receptor blocker medication on important renal and other outcomes are ongoing or recently completed. 44–46 The modest association between nadir hemoglobin concentration on postoperative day 1 and AKI in model 2 is consistent with previous data showing an association between postoperative bleeding and AKI in patients undergoing noncardiac surgery. 10 However, the POISE-3 trial of tranexamic acid versus placebo in patients undergoing noncardiac surgery found no effect of this strategy on AKI despite reducing both major bleeding and the proportion of patients administered a perioperative packed red cell transfusion, highlighting the complexity of the anemia–AKI association.…”
Section: Discussionsupporting
confidence: 89%
“…Nonetheless, CCBs have no deleterious effects throughout the perioperative phase and to be maintained. Another analysis revealed that lower incidence of mortality and MI were associated with CCBs [25].…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that ongoing pragmatic multicentre trials examining the management of RAS inhibitors in patients age ≥18 yr undergoing noncardiac surgery should consider using natriuretic peptide biomarkers to refine interpretation of their data. 34 , 35 , 36 Because two large database studies in noncardiac 37 and cardiac surgery 38 have identified that failure to restart RAS inhibitors is strongly associated with excess morbidity and mortality, further work is required to establish whether serial NT-proBNP measurements can help guide recommencing this drug class. This is particularly relevant given that acute hypertension is independently associated with myocardial injury, 39 most likely through elevated preload causing stretch-induced cardiomyocyte stress.…”
Section: Discussionmentioning
confidence: 99%